PRAKTYCZNO-TEOLOGICZNE RECEPCJE PONTYFIKATU JANA PAWŁA II: ROZWÓJ TEOLOGII COMMUNIO W METODOLOGII PASTORALNEJ - Kießig, Sebastian; Branner, Magdalena (Studia Pastoralne, 2023)
The essay Practical-Theological Reception in the Pontificate of Pope John Paul II: The Development of a Theology of Communio as a Pastoral Methodology takes initially a close look at the position of the Catholic Church, which was changed during the time of the Second Vatican Council. Then the essay discusses the Extraordinary General Assembly of the Synod of Bishops in 1985. At the Synod, communio was identified as a key concept of the Second Vatican Council’s theology. Pope John Paul II supported this development and accented the significance of a practical-theological understanding of communio for a secular world. Finally, this essay gives a summary about these concepts of the theology of communion, which were discussed during the papacy of John Paul II and are continued today in the new developments.